Epidemiology of admissions with respiratory illnesses: a single tertiary centre experience - Das, Satyaki; Ray, Swapan Kumar; Mukherjee, Mallar; Maitra, Anirban; Chatterjee, Kripasindhu; Sen, Sukanta (International Journal of Contemporary Pediatrics, 2017)
Background: Respiratory illnesses in children form a substantial disease burden in emergency care, outpatients and hospitalised patients. Studies exploring the pattern of emergency room visits and hospitalization for individuals with respiratory complaints could inform decisions regarding the effective organisation and planning of health services. Methods: The present prospective observational study was conducted in children between one month to 18 years of age admitted with acute respiratory illness at Institute of Child Health, Kolkata from1st of February 2015 - 28th of February 2015. Results: Preliminary data shows that most of them were diagnosed provisionally as pneumonia (30%) followed by wheeze associated lower respiratory infection (WALRI) (29%). Approximately 10% of admitted patients required PICU support. Antibiotics and bronchodilators were the most commonly used medications. Conclusions: CRP is significantly elevated in bacterial respiratory tract illnesses but a normal or low CRP does not exclude bacterial infection. Best practice may be to avoid antibiotics where possible unless clinically indicated and hospital courses determine so.